Analisis Laporan Keuangan Sebagai Alat Untuk Mengukur Kinerja Keuangan Pada Koperasi Bhinneka Henggi Mas Fakfak (JURNAL ULET (Utility, Earning and Tax), 2023)
ABSTRACTThis research was conducted with the aim of knowing the financial performance of the Bhinneka Henggi Mas Fakfak Cooperative for the last three years. The method used is descriptive method. This study obtained data in the form of transaction data, balance reports and remaining business results owned by the Bhinneka Henggi Mas Fakfak Cooperative. The results of the Bhinneka Henggi Mas Fakfak Cooperative study concluded that it had good financial performance from each measuring instrument used. This study uses a ratio formula consisting of profitability ratios and activity ratios. In the profitability ratio to analyze how much profit from the capital and assets owned by the Bhinneka Henggi Mas Fakfak Cooperative with several ratio indicators namely Net Profit Margin, Return on Assets and Return on Equity. While the activity ratio to measure how effective and efficient the performance of the Bhinneka Henggi Mas Fakfak Cooperative management is with the accounts receivable turnover ratio indicator.